Development of a Routines-Based Early Childhood Intervention model - Hughes-Scholes, Carolyn H.; Gavidia-Payne, Susana (Educar em Revista, 2016)
The Early Childhood Intervention (ECI) literature recommends that intervention is embedded within everyday routines that occur in the natural environment. However, little research has examined the implementation of routines-based models of ECI. The aim of this paper was to describe the development of a Routines-Based Early Childhood Intervention (RBECI) model. The RBECI model consists of four key components: a) Routines-Based Interviews (RBIs); b) participation-based goals; c) home visits; and d) community consultations. Empirical evidence supporting each component of the model is provided, and results from a preliminary evaluation of the implementation of the model are discussed. Further research is required evaluating processes involved in the implementation of the model by ECI professionals and its impact on children and families.